2021
DOI: 10.1021/acsmedchemlett.1c00399
|View full text |Cite
|
Sign up to set email alerts
|

2-Imidazole as a Substitute for the Electrophilic Group Gives Highly Potent Prolyl Oligopeptidase Inhibitors

Abstract: Different five-membered nitrogen-containing heteroaromatics in the position of the typical electrophilic group in prolyl oligopeptidase (PREP) inhibitors were investigated and compared to tetrazole. The 2-imidazoles were highly potent inhibitors of the proteolytic activity. The binding mode for the basic imidazole was studied by molecular docking as it was expected to differ from the acidic tetrazole. A new putative noncovalent binding mode with an interaction to His680 was found for the 2-imidazoles. Inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…To study the effect of compounds on early phases of αSyn aggregation, αSyn dimerization was assessed by a PCA that has been described in the study by Savolainen et al and used by us in several studies. ,, Briefly, N2A cells were seeded on 96-well plates (Isoplate white wall, PerkinElmer Life Sciences) at a density of 13,000 cells/well and transfected with 25 ng of both αSyn-Gluc1 and αSyn-Gluc2 or 50 ng mock plasmid as a control by using Lipofectamine 3000 (L3000001; ThermoFisher Scientific) as the transfection reagent. Forty-eight hours post-transfection, cells were incubated for 4 h with study compounds (10 μM) in DMEM without phenol red (11039021; ThermoFisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the effect of compounds on early phases of αSyn aggregation, αSyn dimerization was assessed by a PCA that has been described in the study by Savolainen et al and used by us in several studies. ,, Briefly, N2A cells were seeded on 96-well plates (Isoplate white wall, PerkinElmer Life Sciences) at a density of 13,000 cells/well and transfected with 25 ng of both αSyn-Gluc1 and αSyn-Gluc2 or 50 ng mock plasmid as a control by using Lipofectamine 3000 (L3000001; ThermoFisher Scientific) as the transfection reagent. Forty-eight hours post-transfection, cells were incubated for 4 h with study compounds (10 μM) in DMEM without phenol red (11039021; ThermoFisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…6,10,23 By studying different PREP inhibitors, we have demonstrated that the structure−activity relationships (SARs) for inhibition of the proteolytic activity and modulation of PPImediated functions, αSyn dimerization and autophagy, are disconnected in the way that some weak PREP inhibitors are highly effective modulators of the PPIs and some highly potent inhibitors do not affect the PPIs at all. 17,24,25 In an αSyndimerization assay performed with PREP knock-out (PREP-KO) cells, the effect of all PREP inhibitors on αSyn dimerization was lost, demonstrating that their effect is the result of an interaction with PREP. 17 As PREP is a highly dynamic protein and inhibitor binding has been reported to restrict its conformational freedom, 26,27 our hypothesis is that the functions of PREP are dependent on what conformations PREP can adopt, and these dynamic features can be regulated differently by different ligands.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,11 Remarkably, experimental studies of PREP suggest that not all PREP inhibitors affect syneculein aggregation at the same level. 12,13…”
Section: Introductionmentioning
confidence: 99%
“…24–26 They differ in the way of binding (KYP 2047 binds covalently to PREP, whereas SUAM 1221 and S 17 092 do not) and inhibition efficacy (KYP 2047 is a potent inhibitor, whereas S 17 092 and SUAM 1221 are weak inhibitors with the IC 50 values 0.2 nM, 27 1.5 nM, 26 and 2.0 nM, 28 respectively). 12,13 More importantly, it has been shown that these inhibitors differently affect dimerisation of α-synuclein – 25%, 20% and the lack of reduction of α-synucleins interaction. 12…”
Section: Introductionmentioning
confidence: 99%
“…Imidazoles are also privileged heterocyclic rings that are ubiquitous throughout natural and synthetic compounds, many of which boast a variety of biological activities (Figure ), including antitumor (Compound A), antiviral, anti-HIV (Compound B), antibacterial, and anti-inflammatory (SB216995), by acting as inhibitors of Bruton’s tyrosine kinase (BTK), prolyl oligopeptidase (PREP), and other enzymes. For example, temozolomide and nilotinib have been approved for use to treat cancer; losartan and losartan hydrochlorothiazide are marketed antihypertensive drugs; ketoconazole, miconazole, econazole, and clotrimazole are well-known antifungal agents; and metronidazole, ornidazole, tinidazole, and secnidazole are anti-infective agents used to treat various bacterial and protozoan infections.…”
Section: Introductionmentioning
confidence: 99%